2021
DOI: 10.1101/2021.09.25.21263798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Transmission Potential and Policy Changes in South Carolina, February 2020 – January 2021

Abstract: Introduction: We aimed to examine how public health policies influenced the dynamics of COVID-19 time-varying reproductive number (Rt) in South Carolina from February 26, 2020 to January 1, 2021. Methods: COVID-19 case series (March 6, 2020 - January 10, 2021) were shifted by 9 days to approximate the infection date. We analyzed the effects of state and county policies on Rt using EpiEstim. We performed linear regression to evaluate if per-capita cumulative case count varies across counties with different pop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…School reopening has been reported by several studies to increase transmission of SARS-CoV-2. [39] , [40] , [41] In our study, the Policy Change R t increase after school reopening was statistically significant in Iberia and East Baton Rouge parishes, Louisiana (75 th and 100 th percentile population size) and Hinds, Mississippi (100 th percentile size). A mathematical modeling study on school reopening reported that it was associated with increased risk in urban regions.…”
Section: Discussionmentioning
confidence: 45%
“…School reopening has been reported by several studies to increase transmission of SARS-CoV-2. [39] , [40] , [41] In our study, the Policy Change R t increase after school reopening was statistically significant in Iberia and East Baton Rouge parishes, Louisiana (75 th and 100 th percentile population size) and Hinds, Mississippi (100 th percentile size). A mathematical modeling study on school reopening reported that it was associated with increased risk in urban regions.…”
Section: Discussionmentioning
confidence: 45%